Effect of STAD Cooperative Learning with Visual Media on Geography Achievement of Tenth-Grade Students in Indonesia - Vinsensia Lorensa Nahak; Sunimbar Sunimbar; Agustinus Hale Manek (Tinta Emas Publisher, 2025)
This study aims to determine the effect of the STAD type cooperative learning model assisted by visual media on geography learning outcomes in class X students of Webriamata State Senior High School, Malaka Regency. The background of this study is based on the low learning outcomes of students due to the absence of a learning model applied by the teacher. The learning process is only centered on the role of the teacher, while students only receive learning materials delivered by the teacher. This situation gradually makes students become bored and appear less enthusiastic in learning. This type of research is a quantitative research experimental method with a Quasi Experimental Design. The population in this study were class X students consisting of 3 classes totaling 90 students with research samples namely class XA and class XB students totaling 60 students. The test instrument used to determine student learning outcomes is a test. Data analysis used is using a t-test to determine student learning outcomes. The results of the study show that the STAD type cooperative learning model can affect student learning outcomes, evidenced by the results of the independent sample T-test which shows a sig. (2-tailed) value of 0.000 <0.05, so Ho is rejected and H1 is accepted. The difference in the results of student learning scores is indicated by the difference in the average N-gain score of the experimental class which obtained an average score of 78.83, higher than the control class with an average score of 57.18.